Refined atrial fibrillation screening and cost-effectiveness in the German population. Issue 6 (10th August 2021) - Schnabel, Renate B; Wallenhorst, Christopher; Engler, Daniel; Blankenberg, Stefan; Pfeiffer, Norbert; Spruenker, Ngoc Anh; Buettner, Matthias; Michal, Matthias; Lackner, Karl J; Münzel, Thomas; Wild, Philipp S; Martinez, Carlos; et al.
Abstract : Objective: Little is known on optimal screening population for detecting new atrial fibrillation (AF) in the community. We describe characteristics and estimate cost-effectiveness for a single timepoint electrocardiographic screening. Methods: We performed a 12-lead ECG in the German population-based Gutenberg Health Study between 2007 and 2012 (n=15 010), mean age 55±11 years, 51% men and collected more than 120 clinical and biomarker variables, including N-terminal pro B-type natriuretic peptide (Nt-proBNP), risk factors, disease symptoms and echocardiographic variables. Results: Of 15 010 individuals, 466 (3.1%) had AF. New AF was found in 32 individuals, 0.2% of the total sample, 0.5% of individuals aged 65–74 years and predominantly men (86%). The classical risk factor burden was high in individuals with new AF. The median estimated stroke risk was 2.2%/year, while risk of developing heart failure was 21% over 10 years. In the 65–74 year age group, the cost per quality-adjusted life-year gained resulting from a single timepoint screening was €30 361. In simulations, the costs were highly sensitive to AF detection rates, proportion of treatment and type of oral anticoagulant. Prescreening by Nt-proBNP measurements was not cost-effective in the current setting. Conclusions: In our middle-aged population cohort, we identified 0.2% new AF by single timepoint screening. There was a significant estimated risk of stroke and heart failure in these individuals. Cost-effectiveness for screening may be reached in individuals aged 65 years and older. The simple age cut-off is not improved by using Nt-proBNP as a biomarker to guide a screening programme.